INNOVATIVE EDUCATION MODEL IN MADRASAH: A LITERATURE REVIEW - Syarip (Irfani, 2024)
Educational innovation has become an essential requirement for madrasas in responding to the challenges of globalization, digitalization, and the evolving characteristics of twenty-first-century learners. This study aims to examine and synthesize scholarly literature related to innovative education models implemented in madrasas, with a particular focus on leadership, pedagogy, curriculum integration, digital transformation, and character education. Using a qualitative literature review approach, this study analyzes peer-reviewed journal articles, academic books, and relevant policy documents from national and international sources. The findings indicate that innovative leadership plays a crucial role in fostering institutional adaptability and improving educational quality. Furthermore, the integration of student-centered learning models, digital technologies, and character-based education significantly enhances students’ academic competencies, moral development, and digital literacy. However, a gap remains between conventional teaching practices and the competencies required in the twenty-first century, particularly in critical thinking, creativity, collaboration, and communication. This study concludes that sustainable educational innovation in madrasas requires systemic curriculum reform, continuous teacher professional development, and strong stakeholder collaboration. The findings contribute to the development of a conceptual framework for innovative madrasa education that balances Islamic values with modern educational demands.